Mutation Testing Effectiveness - An Empirical Analysis on Java Mutation Testing Tools - Luís Carlos de Sousa Pinto (2022)
Software testing is no longer merely a passing fad in software development models. Unit testing, which enables programmers to test each component separately, is one of the most widely used methodologies today. But how can a test suite be accurately evaluated, and how can developers have confidence that their code will not fail or provide unexpected results? That's where mutation testing comes in. Mutation testing is a powerful technique and has an active research state with a history of more than 40 years. It is a complex and computationally expensive testing approach that is seen primarily as a resource-intensive activity when compared to other testing methods. Having support from automated tools is essential for carrying out mutation testing if one want to develop it into a testing method that is both applicable in practice and usable across the industry.